Synthesis and Identification of New Macrocyclic Ligand and Study its Pharmaceutical Properties as Anti-bacterial Reagent by Using Molecular Docking Study - Ali M. Mohamed (Journal of Global Pharma Technology, 2016)
The macrocyclic ligand (5, 7, 12, 14-tetraisobutyl-5, 12-dimethyl -1, 4, 8, 11-tetraazacyclotetradeca-7, 14-diene) was prepared by the reaction between ethylene diamine and 4-methyl pentan-2-one with the help of the perchloric acid as a precipitant reagent. It characterized by FTIR, 1HNMR and UV –Visible techniques. The prepared macrocyclic ligand combine with protein by the application of molecular docking study and it compared with a well-known and standard drug which is gentamycin. The results indicated that the recorded compound is very effective against the toxic bacteria on its cell area and may be in the future become an effective treatment regent by conduct further studies.Keywords: Macrocyclic ligand, Molecular Docking, Gentamycin, Staphylococcus aureus.